Hierarchical neural processing in γ oscillations for syntactic and semantic operations accounts for first- and second-language epistemology - Dekydtspotter, Laurent; Miller, A. Kate; Swanson, Kyle; Cha, Jih-Ho; Xiong, Yanyu; Ahn, Jae-Hyun; Gilbert, Jane A.; Pope, Decker; Iverson, Mike; Meinert, Kent (Frontiers in Human Neuroscience, 2024)
We discuss event-related power differences (ERPDs) in low-and broadband-γ oscillations as the embedded-clause edge is processed in wh-dependencies such as Which decision regarding/about him/her did Paul say that Lydie rejected without hesitation? in first (L1) and second language (L2)French speakers. The experimental conditions manipulated whether pronouns appeared in modifiers (Mods; regarding him/her) or in noun complements (Comps; about him/her) and whether they matched or mismatched a matrix-clause subject in gender. Across L1 and L2 speakers, we found that anaphora-linked ERPDs for Mods vs. Comps in evoked power first arose in low γ and then in broadband γ. Referential elements first seem to be retrieved from working memory by narrowband processes in low-γ and then referential identification seems to be computed in broadband-γ output. Interactions between discourse-and syntax-based referential processes for the Mods vs. Comps in these ERPDs furthermore suggest that multidomain γ-band processing enables a range of elementary operations for discourse and semantic interpretation. We argue that a multidomain mechanism enabling operations conditioned by the syntactic and semantic nature of the elements processed interacts with local brain microcircuits representing features and feature sets that have been established in L1 or L2 acquisition, accounting for a single language epistemology across learning contexts.